2023
DOI: 10.1093/braincomms/fcad113
|View full text |Cite
|
Sign up to set email alerts
|

Predictive blood biomarkers and brain changes associated with age-related cognitive decline

Abstract: Growing evidence supports the use of plasma levels of tau phosphorylated at threonine 181 (p-tau181), amyloid-β, neurofilament light (NfL), and glial fibrillary acidic protein (GFAP) as promising biomarkers for Alzheimer’s disease. While these blood biomarkers are promising for distinguishing people with Alzheimer’s disease from healthy controls, their predictive validity for age-related cognitive decline without dementia remains unclear. Further, while p-tau181 is a promising biomarker, the distribution of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 130 publications
0
15
0
Order By: Relevance
“…We also assessed internalization of synapses by microglia using Syn1 colocalization with the microglial lysosomal marker CD68 ( Figure 2 A), which was also confirmed by super-resolution Airyscan microscopy ( Figure S1 E). CD68 labels both microglia and macrophages, and in the cortical neuropil regions examined from our cases, we observed that CD68-positive cells were also positive for IBA1 and the microglial marker TMEM119 24 , 25 ( Figure S1 G). We found a significant increase in the volume of colocalization between CD68 and Syn1 in AD compared with aged controls (p = 0.0024) and in AD compared with midlife controls (p = 0.0096), suggesting increased synaptic ingestion by microglia in disease ( Figure 2 B).…”
Section: Resultsmentioning
confidence: 57%
See 1 more Smart Citation
“…We also assessed internalization of synapses by microglia using Syn1 colocalization with the microglial lysosomal marker CD68 ( Figure 2 A), which was also confirmed by super-resolution Airyscan microscopy ( Figure S1 E). CD68 labels both microglia and macrophages, and in the cortical neuropil regions examined from our cases, we observed that CD68-positive cells were also positive for IBA1 and the microglial marker TMEM119 24 , 25 ( Figure S1 G). We found a significant increase in the volume of colocalization between CD68 and Syn1 in AD compared with aged controls (p = 0.0024) and in AD compared with midlife controls (p = 0.0096), suggesting increased synaptic ingestion by microglia in disease ( Figure 2 B).…”
Section: Resultsmentioning
confidence: 57%
“…Interestingly, women had significantly more synaptic ingestion by astrocytes when normalized to GFAP burden (p = 0.015). To confirm synaptic ingestion by astrocytes with a sub-diffraction limit technique, we re-analyzed a recently published array tomography dataset, 24 and confirmed at sub-synaptic resolution that synapses are within GFAP-positive astrocytes ( Figures S1 J and S1K).
Figure 1 Astrocytes ingest more synapses in Alzheimer’s disease compared with midlife and aged controls (A) Confocal images of immunostaining with orthogonal views (left) and three-dimensional reconstructions of stacks (right) of midlife control, aged control, and Alzheimer’s disease showing ingestion of synapsin 1 (Syn1, green) by astrocytes (GFAP, magenta) in human brain sections.
…”
Section: Resultsmentioning
confidence: 91%
“…This suggests that further evidence is required to establish what these biomarkers truly represent and their utility as surrogate biomarkers with degree of reduction required in the specific context of each therapeutic modality, epitope and mechanism of action (discussed in further sections of this review). Recent evidence suggests that some phosphorylated tau fluid biomarkers may in part reflect synaptic dysfunction via accumulation and release of oligomeric phosphorylated tau, and also plaque-associated dystrophic neurites that contain oligomeric phosphorylated tau [ 71 , 72 ].…”
Section: Ptau181 Ptau217 and Ptau231 Are Not Exclusive Biomarkers For...mentioning
confidence: 99%
“…In addition, it has been shown that GFAP levels in both CSF and plasma correlate with cognitive and biological measures of AD progression. For instance, elevated plasma and GFAP levels are associated with lower cognitive performance and steeper cognitive decline ( 59 , 60 ). Moreover, recent studies have shown that higher GFAP plasma levels correlate particularly with amyloid burden measured both by CSF and amyloid-PET quantification in opposition to Tau burden ( 46 , 61 , 62 ).…”
Section: Brain-immune System Crosstalk In Alzheimer’s Diseasementioning
confidence: 99%